Penerapan Bauran Pemasaran dalam Meningkatkan Volume Penjualan Produk Udang Beku di Pt. Dachan Mustika Aurora - Nurul Fitri; Sulkifli Sulkifli; Nur Alam Kasim (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
One of the efforts made by the company to increase and optimize its sales volume is by implementing a marketing mix which has a combination of four variables or activities which are the core of the company system, which consists of: product, price structure, promotional activities, and distribution system. The aim of this research is to determine the influence of marketing mix variables in increasing sales volume. The type of research used in this research uses a quantitative approach. The population of this research is employees from the buyer. The sampling technique used purposive sampling with a sample of 11 respondents. The analysis technique in this research uses multiple linear regression with SPSS version 22. The results of this research show that the marketing mix as a whole has a simultaneous effect on increasing sales volume through f testing. This is proven by the calculated f value of 36.898 > f table 4.965, while the significant value of f is 0.000 < α = 0.05. From the results of the t test, product, price, promotion and place has a positive and significant effect on sales.